AN IMPLEMENTATION OF RECOGNITION LETTER AND NUMBER BASED ON MOBILE FOR EARLY CHILDHOOD KINDERGARTEN IT-AL FATIH - Heni Wulandari; Suherman Suherman; Leni Marlina (INFOKUM, 2022)
An Early childhood education could be defined as all efforts in facilitated a development and learning of children from birth to six years of age through provision of various experiences and stimuli that are developing. Kindergarten (TK) IT AL Fatih is one of schools that educates early childhood, where the school is located at Pelaksanaan I street No.02 steet IV. At the school there is no means of learning children through interactive learning media, in learning to recognize letters and numbers the teacher still uses the lecture method so that the learning process to children can cause boredom and boredom. Interactive learning in the form of audio visual using mobile-learning technology is a learning system needed by early childhood to be responsive and encourage the emergence of teacher innovation and creativity in creating and developing a conducive educational climate in kindergarten IT AL Fatih. The implementation of activities uses an approach method by conducting direct socialization and explaining to teachers and children how the application of letter and number recognition in mobile-based early childhood can increase teacher productivity and increase children's interest in learning. The results of the evaluation during the activity process received very good responses, as evidenced by the questionnaire evaluation, 75% of which stated strongly agree (SS) and 25% stated agree (S).